Contribution Of Arm Muscle Power , Lemb Muscle Power , And Hands Eye Coordination On Ability Jump Shoot On Students Ekstrakuricular Sman 1 Pasir Penyu Basketball - M. Adrian; Oki Candra (CV. AFDIFAL MAJU BERKAH, 2023)
The goal to be achieved in this study was to find out how much the contribution of arm muscle power, leg muscle power and hand eye coordination to the ability to jump shoot in basketball extracurricular students at SMAN 1 Pasir Penyu. This type of research is research using multiple linear regression tests , The multiple linear regression method aims to determine how much influence the independent variables have on the existing dependent variable. In this research, the variable (X 1 ) is arm muscle power, variable (X 2 ) is leg muscle power, variable (X 3 ) is hand eye coordination and the dependent variable (Y) is jump shoot ability . The research was conducted at SMAN 1 Pasir Penyu on basketball extracurricular students . SMAN 1 Pasir Penyu is located right in Indragiri Hulu Regency . The time used to carry out this research was for two days starting from the 5th of March 2023 And the 9th of march 202 3 . The sample was taken by Total Sampling, where the entire population was used as a sample, amounting to 12 extracurricular basketball students at SMAN 1 Pasir Penyu . The instruments to be used in this study were the Two Hand Medicine Ball Chest Pass Test, the Vertical Jump Test, the Hand Eye Coordination Test and the Jump Shoot Ability Test . Based on the calculation results, there is a contribution of arm muscle power, leg muscle power and hand eye coordination to the ability to jump shoot in basketball extracurricular students at SMAN 1 Pasir Penyu by 9.4% with a score in the low category .